Drawing Planar Graphs with Large Vertices and Thick Edges - Barequet, Gill; Goodrich, Michael; Riley, Chris (Journal of Graph Algorithms and Applications, 2004)
We consider the problem of representing size information in the edges andvertices of a planar graph. Such information can be used, for example, todepict a network of computers and information traveling through thenetwork. We present an efficient linear-time algorithm which draws edgesand vertices of varying 2-dimensional areas to represent the amount ofinformation flowing through them. The algorithm avoids all occlusions ofnodes and edges, while still drawing the graph on a compact integer grid. <!---->